2017
DOI: 10.1590/1807-1929/agriambi.v21n12p840-845
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and crop coefficients of Moringa oleifera under semi-arid conditions in Pernambuco

Abstract: Efficient water use in agriculture is fundamental, especially in semi-arid regions where water scarcity is intense. The aim of this study was to estimate water requirements and crop coefficients in the different phenological stages of Moringa oleifera. The experiment was carried out from February to April 2015 at the Experimental Unit for Reuse and Hydrological Management, located in Mutuca, PE (7º 15’ 18’’ S, 35º 52’’ 40’’ W, 550 m). A lysimeter was used to estimate crop evapotranspiration. Reference evapotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
6
0
4
Order By: Relevance
“…Heavy rainfall events can occur in the region, as already reported by [51], with a total of 120 mm in a single day, in February 2015. According to [3], there is a trend of climatic changes for the rainfall pattern for the Brazilian Northeast, with an increase in the number of extreme events being expected, as well as a reduction in the number of rainy days, which could result in a greater number of more intense and concentrated events.…”
Section: Rainfall and Irrigation Depths During Sorghum Cultivationsupporting
confidence: 65%
See 1 more Smart Citation
“…Heavy rainfall events can occur in the region, as already reported by [51], with a total of 120 mm in a single day, in February 2015. According to [3], there is a trend of climatic changes for the rainfall pattern for the Brazilian Northeast, with an increase in the number of extreme events being expected, as well as a reduction in the number of rainy days, which could result in a greater number of more intense and concentrated events.…”
Section: Rainfall and Irrigation Depths During Sorghum Cultivationsupporting
confidence: 65%
“…This result is reinforced by the fact that the irrigated field has been used for several crop cultivations since 2009, using wastewater from the local district. [67] presented results for color cotton cultivation, while [51] developed the cultivation of moringa, investigating soil and salinity dynamics using drainage lysimeters. Soil retention properties were analyzed, and similar salinity dynamics were confirmed for the 0-20 cm, 20-40 cm, and 40-60 cm layers.…”
Section: Effects Of Irrigation Depths With Wastewater and Mulch On Soil Electrical Conductivity And Organic Mattermentioning
confidence: 99%
“…O solo da área é caracterizado de acordo com a classe de textura como Areia Franca, com teor de areia de 83,92 e 82,92%, argila de 12,44 e 13,44%, silte de 3,64 e 3,64%, densidade do solo de 1,4 e 1,51 g cm -3 , capacidade de campo de 0,3 e 0,33 cm³ cm -3 e ponto de murcha permanente de 0,2 e 0,2 cm³ cm -3 para as camadas 0-20 e 20-40 cm, respectivamente (Santos et al, 2017). O solo é classificado como Planossolo Háplico Sálico Sódico Hipereutrófico (Miranda, 2010), e dotado de sistema de drenagem subterrânea.…”
Section: Methodsunclassified
“…Estudos sobre a viabilidade de produção agrícola associado ao reuso de água têm sido largamente pesquisado e analisado em condições de campo no Agreste pernambucano, na Estação de Tratamento de Esgoto (ETE) de Mutuca em Pesqueira, com os cultivos do algodoeiro (Gossypium hirsutum L.), girassol (Helianthus annuus L.), moringa (Moringa oleífera L.) e mamoneira (Ricinus communis L.) (Miranda, 2010;Lima et al, 2012;Santos, 2015;Santos et al, 2017). Nesta ETE são desenvolvidas diversas ações de ensino, pesquisa e extensão, voltadas para monitoramento agroclimatológico participativo, para a conservação de recursos hídricos e para a produção agrícola.…”
Section: Introductionunclassified
“…When assessing the relationship between ET c and ET o , Graham et al, (2016) found that ET c explained 97% of ET o . Santos et al (2017) evaluated the regression between ET c and ET o for three of the phenological stages of Moringa, and observed an R² of 0.99 for all stages.…”
Section: Climatic Conditions and Crop Coefficient (K C )mentioning
confidence: 99%